Anlysis Of Chicken Floss Quality From Spen Layer Hent - Safitri, Febri; Holinesti, Rahmi (Universitas Negeri Padang, 2023)
This study aims to increase the economic value of spent layer hens by using them in a form of a food product, namely chicken floss. The research was conducted in November 2022 at the Catering Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University. The type of research used was an experiment with a completely randomized design (RAL) method to compare the quality of chicken floss between broiler and spent layer hens. The used are primary data obtained directly from three (3) expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of chicken floss. After obtaining the data, it is then tabulated in tabular form and Independent Sample T-test (Poilet variance) is performed. The results of the comparative t-test showed that there were significant differences in the quality of chicken floss in terms of color and texture. The best treatment was the X₁ with a color quality of 3.44 for the golden yellow color category, aroma quality of 3.78 for the fragrant scent category, texture quality of 3.56 for the fine fibrous texture category, and taste at 4. 00 categories of savory flavors.